Application Software of Financial Statements Compilation for Monitoring Financial Growth - Listiani, Dhanik; Muhamad, Wardani; Dewi Budiwati, Sari (International Journal of Engineering and Technology, 2019)
The financial statements are essentially financial records regarding the activities of the company or organization during the accounting period and used to provide useful information for a large number of users in making economic decisions. The URO Parts Store concern to use financial statements to monitor their financial growth. However, it does not yet have a well-integrated system, in particular, to record sales transactions and inventory. The process of recording and processing the sales and purchasing transaction data is still done conventionally using ledgers. In addition, the URO Parts Store also does not make financial statements to report the recapitulation of the proceeds, while the financial statement is an important thing that is needed to measure the operating performance of the business during the period as well as decision-making by management. Also, accurate financial performance is used as a basis for predicting the financial position and performance in the future. To answer the needs of URO Parts Store in accordance with its business processes, built an application software application that is able to record and process the sales transaction data. It can present items of information, sales data, purchase data, transaction reports, and financial statements that form the income statement and statement of changes in capital. The result shows that application can generate accurate financial statement during an accounting period.Â Â